Considerations in the application of two dimensional shear wave elastography in muscle. Issue 1 (26th November 2019) - Mackintosh, S.; Young, A.; Lee, A.; Sim, J.
Abstract: There is hope that the development of 2D shear wave elastography (2D‐SWE) technology will enhance clinical assessment of muscles. In addition to structural information obtained from traditional sonography, knowledge of muscle biomechanical properties may add diagnostic value in the investigation of pathological processes and functions of the musculoskeletal system. 2D‐SWE offers benefits over traditional biomechanical testing tools and may be adapted to assess muscle at rest, or in contracted or lengthened states. To date, disparate research methodologies and proprietary technological differences limit comparison of research findings. Consensus guidelines exist for clinical utilisation of elastography in fields such as liver, breast and thyroid imaging. Presently, no such consensus has been reached for 2D‐SWE muscle utilisation. This paper explores the current literature to describe the technical considerations and challenges of 2D‐SWE in the assessment of skeletal muscle.